Correlation of Liquid Volume in Stomach to Electrical Transfer Impedance Measurements Using FIM (Bangladesh Journal of Medical Physics, 2014)
The present work is directed to the measurement of the absolute volume of secreted acid in the stomach using 6-electrode FIM. Stomach acid is important because it has diagnostic applications in diarrhoeal diseases and in anaemia. Through a simplified resistance model this work has predicted that the variation in (Ze-Zs)/Ze with volume of liquid in stomach should be much greater than that of Zs/Ze . The simple resistance model has also predicted that the normalised change in measured transfer impedance (Ze-Zs)/Ze will be proportional to the volume of liquid in the stomach provided the resistivity of the liquid and the depth of stomach from the frontal skin surface is constant. Both these have been verified through real life measurement on two human subjects. This means that the measured transfer impedance change can indeed be related to the volume of saline in stomach. Together with depth information obtained using anatomical markers, it may be possible to obtain the absolute volume using FIM non-invasively. DOI: http://dx.doi.org/10.3329/bjmp.v6i1.19761 Bangladesh Journal of Medical Physics Vol.6 No.1 2013 66-74